Analisis Efektivitas Alat Gali-Muat Menggunakan Metoda Overall Equipment Effectiveness (OEE) untuk Meningkatkan Produksi Overburden di Pit Central PT Saptaindra Sejati Site Adaro Mining Operation - Marta Weri; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2022)
Based on data on stripping production overburden at the Central pit PT Saptaindra Sejati Jobsite Adaro Mining Operation (ADMO), stripping production overburden did not reach the target. This has an impact on operating costs incurred for stripping each BCM (Bank Cubic Meter) of thelayer overburden. To determine the potential for improvement of a production process and the effectiveness of using an equipment, it is necessary to carry out an analysis using the method Overall Equipment Effectiveness (OEE). OEE is known as a totalprogram application productive maintenance that has the ability to clearly identify the root of the problem and its causative factors so as to make improvement efforts more focused. In the analysis process of the OEE formula, themethod is also used Six Sigma to make improvements to the OEE value. Where, Six Sigma is a method for solving problems and improving the overall process. Furthermore, adiagram is used fishbone to find the root of the problem in more detail and an evaluation is carried out by referring to the method formulation six sigma.After analyzing and improving with these methods, the EX350-0005A Li R9400 production exceeds the planned target. However, the OEE value of each digging tool is still <85%, it has not reached the world class OEE value> 85%, it can be concluded that the condition of the equipment is not good. We recommend that you repair the time standby and breakdown again device